(+)‐Sesamin‐oxidising CYP92B14 shapes specialised lignan metabolism in sesame. (11th October 2020) - Harada, Erisa; Murata, Jun; Ono, Eiichiro; Toyonaga, Hiromi; Shiraishi, Akira; Hideshima, Kosuke; Yamamoto, Masayuki P.; Horikawa, Manabu
Summary: Sesamum spp. (sesame) are known to accumulate a variety of lignans in a lineage‐specific manner. In cultivated sesame ( Sesamum indicum ), (+)‐sesamin, (+)‐sesamolin and (+)‐sesaminol triglucoside are the three major lignans found richly in the seeds. A recent study demonstrated that SiCYP92B14 is a pivotal enzyme that allocates the substrate (+)‐sesamin to two products, (+)‐sesamolin and (+)‐sesaminol, through multiple reaction schemes including oxidative rearrangement of α‐oxy‐substituted aryl groups (ORA). In contrast, it remains unclear whether (+)‐sesamin in wild sesame undergoes oxidation reactions as in S. indicum and how, if at all, the ratio of the co‐products is tailored at the molecular level. Here, we functionally characterised SrCYP92B14 as a SiCYP92B14 orthologue from a wild sesame, Sesamum radiatum, in which we revealed accumulation of the (+)‐sesaminol derivatives (+)‐sesangolin and its novel structural isomer (+)‐7´‐episesantalin. Intriguingly, SrCYP92B14 predominantly produced (+)‐sesaminol either through ORA or direct oxidation on the aromatic ring, while a relatively low but detectable level of (+)‐sesamolin was produced. Amino acid substitution analysis suggested that residues in the putative distal helix and the neighbouring heme propionate of CYP92B14 affect the ratios of its co‐products. These data collectively show that the bimodal oxidation mechanism of (+)‐sesamin might be widespread across Sesamum spp., and that CYP92B14 is likely to be a key enzyme in shaping the ratio of (+)‐sesaminol‐ and (+)‐sesamolin‐derived lignans from the biochemical and evolutionary perspectives. Significance Statement: In Sesamum indicum (sesame), SiCYP92B14 oxidises (+)‐sesamin, a health‐promoting compound, to either (+)‐sesaminol or (+)‐sesamolin via two distinct reaction mechanisms. The identification and biochemical characterisation of SrCYP92B14 from wild sesame, S. radiatum, revealed that SrCYP92B14 oxidises (+)‐sesamin predominantly to (+)‐sesaminol, which corroborates with the lignan profile of S. radiatum, thus highlighting the relevance of CYP92B14 proteins in shaping the molar ratio of (+)‐sesaminol and (+)‐sesamolin derivatives that accumulate in Sesamum spp.